English advance level [ (Lesson For Life International, 2007)
Lessons for Life - English is a full immersion, multimedia language learning program that caters to all individual learning styles. Its friendly user-interface and simple, intuitive and clear navigation makes learning with Lessons for Life - English an enjoyable and rewarding experience. Lessons For Life, English - Advanced Level is comprised of :- 10 units- 90 plus interactive activities, grammar exercises and tests & 100 practical conversations.